An evaluation of the biocompatibility and osseointegration of novel glass fiber reinforced composite implants: In vitro and in vivo studies. Issue 3 (March 2018) - Chan, Ya-Hui; Lew, Wei-Zhen; Lu, Emily; Loretz, Thomas; Lu, Luke; Lin, Che-Tong; Feng, Sheng-Wei
Graphical abstract: Highlights: Three novel bioactive glass fiber (Bio-fiber)-reinforced composite materials have been successfully developed and firstly evaluated. These new materials have the characteristics of moderately rough surface, hydrophilicity and exposure of glass fibers. These new materials exhibited good cell attachment, cell proliferation and differentiation. The Bio-fiber-reinforced composite implants markedly enhanced bone regeneration in the rabbit femoral condyle model. Abstract: Objectives: The aim of this study was to evaluate the in vitro biocompatibility and in vivo osseointegration of three novel bioactive glass fiber reinforced composite (GFRC) implants and to compare these with metal (Ti6Al4V) implants. Methods: The surfaces of these experimental substrates were characterized by scanning electron microscopy (SEM), a 2D profilometer and by contact angle measurement. In vitro biological performance was assessed using MG-63 human osteoblast-like cell morphology, cell proliferation assays and the alkaline phosphatase (ALP) activity testing. Furthermore, in vivo osseointegration performance was examined by installing samples into rabbit femurs and evaluated the results using micro-CT, histology and histomorphometrical analysis; these assessments were carried out after 1, 2, 4 and 8 weeks of healing. Results: The results showed that moderate surface roughness, moderate hydrophilic exposure and moderate homogenous exposure of bioactive glass fibers were present for all of the GFRC substrates. Furthermore, MG-63 cells, when cultured on all of the GFRC substrates, grew well and exhibited a more differentiated phenotype than cells grown on titanium alloy (Ti6Al4V) substrate. Histological evaluation revealed more newly-formed bone regeneration within the thread of the GFRC implants during the initial healing period. In addition, the novel GFRC implants with a bioactive Bio-fiber structure and glass particles within the epoxy resin matrix showed better bone volume/tissue volume (BV/TV) values at 4 weeks and this was accompanied by bone-implant contact (BIC) values at 8 weeks comparable to the Ti6Al4V group. Significance: These findings demonstrated that novel GFRC implants seem to show improved osteogenesis and osseointegration functionality and have potential as a substitute for Ti6Al4V, or other metal-based materials, when used for clinically dental and orthopedic applications.